Desempenho e características de carcaça e da carne de cordeiros alimentados com silagem de bagaço de laranja - Santos, Ana Caroline Pinho dos (2014)
The work aimed to evaluate the effect of substitution of corn for silage of orange (SBL) on performance, carcass characteristics and meat in live weight components, tissue composition of the leg of Santa Inês lambs. Twenty not castrated, with average live weight (LW) of 24.56 kg and approximately five months of age, were kept until they reached 33 kg, fed diets containing increasing levels of SBL replacing corn (0, 33 , 66 and 100% MS). The dry matter intake (DMI) in grams was influenced (P <0.05) by the substitution of corn by SBL, the levels of 66% and 100% showed similar means, 870.22 g / day and 726.02 g / day respectively. IMS at 33% level was similar to that without the inclusion level and the other levels (915.96 g / day). There was a significant difference (P<0.05) for the final PV in relation to replacement levels, the level 100% differed (30.12 kg) level without SBL, and similar levels of 33% and 66% of substitution. The PV slaughter was influenced (P<0.05) the substitution of corn by SBL, the level 100% differed from the other levels, with an average of 28.90 kg. The hot carcass weight and cold carcass weight were influenced (P<0.05) by the substitution of corn by SBL, the 100% level showed lower weight, 13.60 kg and 13.41 kg, respectively, differed significantly levels. There was a significant difference (P<0.05) for the weight of the pallet, rib and loin from the levels of substitution of corn by SBL. The level of 100% substitution showed a lower weight palette (1.267 kg), rib (1.844 kg) and loin (0.470 kg) differing level of 66%. Levels of 0% and 33% showed similar values to other levels, both how palette for loin. For the rib, the level of 100% differed from the 33% level, the levels of 0% and 66% were similar to the others. The weight of skin was influenced (P<0.05) the substitution of corn for silage of orange (SBL), the level of 100% substitution showed lower weight (1.924 kg) compared to the 0% level (2.253 kg) levels 33% and 66% showed similar level of 0% and 100% weight, with averages of 2.053 kg and 2.14 kg respectively. There was a significant difference (P<0.05) for the tongue weight, the level of 0% had lower weight (51.6 g) compared to levels 33% and 66% replacement (76.8 g and 71.8 g) the level of 100% was similar to other levels (71.6 g) weight. The heart was influenced (P <0.05) by the substitution of corn by SBL, the level without the SBL showed higher weight (151 g) compared to the level of 100% (118.4 g), levels 33 and 66% % had similar weights at other levels (141.8 g and 140 g). There was a significant difference (P <0.05) for the liver compared to replacement levels. The 0% level showed higher weight (592 g) compared to levels 33% and 100% (481.8 g and 458.8 g), the level of 66% was similar to other levels (518.6 g) weight. Silage can be used as an alternative source of supply in Santa Ines sheep up to 66% replacement of maize in the conditions under which this work was developed